A renal biopsy-based clinicopathological study of primary tubulointerstitial nephritis in children - Amey, Rojekar; Chitra, Madiwale (Indian Journal of Child Health, 2019)
Background: Inflammation of the tubular and interstitial compartment without involving the glomeruli and vessels is called as primary tubulointerstitial nephritis (TIN), which may be due to varied etiologies. This is relatively uncommon in children as compared to primary glomerular disorders. Infections and drugs are the most common causes of primary TIN worldwide. Objectives: The objectives of the study were to assess primary TIN in pediatric patients using findings from renal biopsies at a tertiary care center of Western India. Materials and Methods: All biopsy-proven cases of primary TIN in pediatric patients over a period of 10 years were included in the study. All cases with glomerular or vascular diseases, or where data were inadequate were excluded from the study. The cases were reviewed in detail for epidemiological data, clinical presentation, etiology, and histomorphological features. Depending on their clinical and morphological features, the cases were categorized into acute, chronic, and granulomatous TIN. Results: A total of 30 cases of primary TIN were assessed with a mean age of 12.4 years and range of 6–18 years. Pedal edema and facial puffiness were the most common symptoms followed by oliguria. The common causes of TIN were drugs, namely antibiotics and non-steroidal anti-inflammatory drugs and infections. Acute TIN was more common than chronic TIN. Conclusion: Primary TIN is an uncommon renal disease in pediatric patients with varied presentations and etiologies. However, early diagnosis by renal biopsy, detailed history, and withdrawal of the offending agent along with prompt treatment helps in recovery and avoids chronic renal damage.